Wanita Karir: Analisis QS. Al-Ahzab: 33 Berbasis Teori Double Movement - Mutiara Cahya Noviani; Azis Muslim (Pascasarjana IAIN Sultan Amai Gorontalo, 2023)
This study aims to answer questions about the law of women's careers in the public sphere, while the verse of the Qur'an studied is Qs. There are several different interpreters in interpreting this verse so there is a gap that occurs in women today. This research uses a hermeneutic approach, namely double movement theory as a theory to know and understand the verse of the Qur'an contextually. The results show that it is permissible for women to have a career in the public sphere as long as it does not harm themselves and their work, and can provide benefits or benefits to the people.